2011
DOI: 10.1155/2011/609537
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Radiation Exposure to the Eyes of the Interventional Pain Physician

Abstract: It is widely accepted that the use of medical imaging continues to grow across the globe as does the concern for radiation safety. The danger of lens opacities and cataract formation related to radiation exposure is well documented in the medical literature. However, there continues to be controversy regarding actual dose thresholds of radiation exposure and whether these thresholds are still relevant to cataract formation. Eye safety and the risk involved for the interventional pain physician is not entirely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
(27 reference statements)
0
17
0
2
Order By: Relevance
“…According to NCRP and international council on radiation protection (ICRP), radiation cataract is deterministic and only occurs when a high-dose threshold is exceeded (17). However, sev-eral studies have shown that radiation-associated opacities occur at much lower (non-threshold) doses (15,18). Recent findings have demonstrated dose-related significant lens opacification in rats after exposure to as little as 100 mGy (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to NCRP and international council on radiation protection (ICRP), radiation cataract is deterministic and only occurs when a high-dose threshold is exceeded (17). However, sev-eral studies have shown that radiation-associated opacities occur at much lower (non-threshold) doses (15,18). Recent findings have demonstrated dose-related significant lens opacification in rats after exposure to as little as 100 mGy (19).…”
Section: Discussionmentioning
confidence: 99%
“…It means that interventional cardiologists and staff working in intervention sites are in situations where radiation doses are high enough to cause lens opacity after a few years if protection is not used. Although the amount of reduction in the cataract risk with the use of protective eyewear is not clear (15), it is established that interventional cardiology personnel may be at risk for cataract without use of ocular radiation protection (12). Use of scattershielding drapes or leaded glasses decreases the operator lens dose by a factor of 5 to 25, but the use of both barriers together (or use of leaded shields) provides maximal protection to the interventional radiologist's eye (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of lead-based glasses is advocated, especially when the risk of "rescatter" (radiation which emanates from within the interventionalist's head, or so-called tertiary exposure) is considered (Cousin et al 1987). As pointed out in a review on exposure risks of interventional pain physicians, studies demonstrate a decrease in transmission rates of 70-90% with appropriate eyewear ("lead" glasses) ( Fish et al, 2011). Moreover, because it is the patient that is the point source of occupational radiation risk coupled with the proximity of the interventional pain physician to the patient, positioning the monitor to require the interventionalist to look 90° (from the patient) with eyewear with side shields could further help reduce eye exposure.…”
Section: Apronsmentioning
confidence: 99%
“…Moreover, because it is the patient that is the point source of occupational radiation risk coupled with the proximity of the interventional pain physician to the patient, positioning the monitor to require the interventionalist to look 90° (from the patient) with eyewear with side shields could further help reduce eye exposure. As stated by Fish et al (2011), "…It is extremely vital for the interventionalist to be cognizant of his/her surroundings. This reiterates the importance of increasing the distance between the physician and the source of the radiation, it also emphasizes decreasing the amount of exposure time, which can both drastically reduce unnecessary radiation via scatter.…”
Section: Apronsmentioning
confidence: 99%
“…В то время как количество и широта интервенционных процедур продолжают увеличиваться, повышаются ли радиационные риски? Хорошо известно, что хрусталик глаза обладает повышенной радиочувствительностью [1]. В специализированной медицинской литературе хорошо описаны побочные эффекты радиационного воздействия на хрусталик глаза, приводящие к его полному или частичному помутнению.…”
unclassified